Anaplastic (undifferentiated) carcinoma of pancreas, an uncommon variant: Diagnosed on endoscopic-guided fine needle aspiration - Md Ali Osama; Pooja Bakshi; Kusum Verma (Indian Journal of Pathology and Microbiology)
Anaplastic carcinoma of pancreas (ACP) are rare pancreatic neoplasms. They are well known to be associated with more aggressive tumor behavior and less favorable prognosis than usual pancreatic ductal adenocarcinoma. Endoscopic-guided fine needle aspiration (EUS-FNA) is now a widely accepted modality in diagnosis of pancreatic lesions. However, only a few reports are available describing cytological features of anaplastic carcinoma. Here, we report two cases of ACP diagnosed on EUS-FNA.